(untitled) (Medical Forum Monthly, 2023)
Objective: This study aims to assess the anti-cancer potential of the Grewia asiatica plant extract against SF767 cell lines, exploring its efficacy as a cost-effective and low side-effect alternative in cancer treatment. Study Design: In Vitro Experimental Study. Place and Duration of Study: This study was conducted at the Institute of Molecular Biology and Biotechnology (IMBB), The University of Lahore, from July 2021 to Dec 2021. Methods: SF767 cell lines are treated with ethanolic Grewia asiatica plant extracts, and their viability is systematically assessed through MTT, crystal violet, trypan blue, and scratch assays. These methods collectively provide insights into the growth rate, metabolic activity, and overall viability of SF767 cells exposed to the plant extract. Results: SF767 cells treated with ethanolic Grewia asiatica plant extracts exhibit a significantly reduced proliferation rate, as indicated by the MTT assay. Both crystal violet and trypan blue assays confirm a substantial inhibition of cell viability. The scratch assay further supports these findings, emphasizing the efficacy of Grewia asiatica in impeding cancer cell proliferation. Conclusion: In conclusion, the Grewia asiatica plant extract demonstrates robust in vitro anti-cancer properties against SF767 cell lines. The observed reduction in tumor cell growth, inhibited metabolic activity, and compromised cell viability underscore the potential therapeutic significance of the plant extract in anti-cancer treatments. Further research, including animal and human trials, is imperative to validate and translate these in vitro findings into practical applications for cancer therapy.